Adoption and implementation of BIM – case study of a Saudi Arabian AEC firm. Issue 3 (2nd July 2018) - Almuntaser, Taqiadden; Sanni-Anibire, Muizz O.; Hassanain, Mohammad A.
Abstract : Purpose: The adoption of building information modeling (BIM) technology in the global architecture, engineering and construction (AEC) industries is steadily increasing. However, developing countries such as Saudi Arabia are still lagging behind. The purpose of this paper is to present a framework for BIM adoption in the AEC industry in Saudi Arabia through a case study. Design/methodology/approach: The study adopted a two-pronged approach. First, the various stages, benefits and challenges of BIM implementation in a local AEC firm's pilot project were documented. Then, a BIM maturity measurement of the pilot project was conducted, and identification of the areas where improvements can be made. Findings: BIM implementation provided several benefits and efficiency gains. These include a faster design processes, effective reuse of information and overall client satisfaction. Challenges faced include a lack of interest by clients and industry stakeholders, inadequate experience of the BIM team, and lack of mentorship from a BIM champion. The findings of the BIM maturity measurement were presented as an implementation framework in the five process areas and ten subject areas of the Project Management Institute's (PMI) project management framework. Originality/value: Though, frameworks, guidelines and protocols have been developed to facilitate the successful adoption of BIM, the issue is not a case of "one size fits all." This study thus introduces the much needed awareness in the research and professional domain in Saudi Arabia. It also presents the proposed framework in the PMI framework, which is an incremental innovation to previous work.